Open capacity calculation method of distribution network. Issue 1 (1st February 2023) - Li, Jianyu; Wang, Jie; Lin, Yujie; Yang, Binhao; Wu, Chengjian
Abstract: At present, there are few methods for quantitative calculation of installed load or new energy for distribution network equipment. Based on this, this paper proposes a calculation method for the open capacity of the distribution network. Firstly, the calculation methods of the open capacity of a 10 kV distribution transformer, 10 kV lines, and high-voltage substation three-level distribution network based on the conventional situation and new power system are studied, respectively. Then the calculation methods of the open capacity of the distribution system based on the conventional case and the new power system are studied, respectively. Finally, the empirical region is selected, and the research results are used for case analysis to verify the effectiveness and operability of the research results.